2002
DOI: 10.1007/s00417-002-0530-7
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in patients with diabetic retinopathy: Visual outcome, progression of diabetic retinopathy, and incidence of diabetic macular oedema

Abstract: Modern cataract surgery seems to have no influence on the progression of diabetic retinopathy. A visual improvement is achieved in the majority of patients with NPDR, but poorer visual outcome is observed in patients developing macular oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 19 publications
4
97
5
1
Order By: Relevance
“…[18][19][20][21] In these studies, the most significant predictor for progression of DR has been the status of the DR at the time of the cataract surgery. [13][14][15][16]22,23 Similarly, diabetic macular oedema has been shown to worsen after cataract surgery, [24][25][26] although controversy remains as to the incidence of this worsening.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] In these studies, the most significant predictor for progression of DR has been the status of the DR at the time of the cataract surgery. [13][14][15][16]22,23 Similarly, diabetic macular oedema has been shown to worsen after cataract surgery, [24][25][26] although controversy remains as to the incidence of this worsening.…”
Section: Introductionmentioning
confidence: 99%
“…Aynı çalışmada makula ödeminin pik yapma insidansı 1. ay olarak belirlenmiş ancak MÖ oranı bir önceki çalışmaya göre daha düşük belirtilmiştir. MÖ insidansı farklı çalışmalarda %29 ile %56 arasında değişmektedir [15,17,18]. Kwon ve ark.…”
Section: Discussionunclassified
“…In diabetic patients however there seems to be a greater predisposition to developing CME or to a worsening of existing ones, although not all studies have confirmed this tendency (14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It is also very useful in the differential diagnosis between diabetic CME, if it appears early in postop, and pseudo-phakic CM with a lower prognosis (15) and which appears typically one month after surgery. Obviously, this also has therapeutic implications (16,18).…”
Section: Discussionmentioning
confidence: 99%